Hardness and modulus of elasticity of atomic layer deposited Al2O3-ZrO2 nanolaminates and mixtures - Jõgiaas, Taivo; Zabels, Roberts; Tarre, Aivar; Tamm, Aile (Elsevier B.V., 2020)
Atomic layer deposition was used to produce 90–105 nm thick alumina-zirconia mixtures and nanolaminate structures on soda-lime glass substrate. The resultant chemical and structural compositions of the thin films were characterized. Hardness and modulus of elasticity were determined by instrumented nanoindentation. The hardness of mixtures and nanolaminates were in the range of 11–15 GPa and moduli in the range of 140–180 GPa ZrO2 with 3.7 mol.-% Al2O3 crystallized in pure tetragonal phase and measured hardness reached about 15 GPa on glass substrate at indentation displacement of about 13 nm. Similar mechanical properties were measured in most thin films, except pure ZrO2, demonstrating insensitivity of mechanical properties to deposition receipt.
This work was funded by the European Regional Development Fund project TK134 “Emerging orders in quantum and nanomaterials”, Estonian Research Agency project PRG4 “Emerging novel phases in strongly frustrated quantum magnets”.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Atomic layer deposition; Nanoindentation; Nanocomposites